Pilot testing of sticker tool method for monitoring DOTS providers under revised national tuberculosis control program in Khammam: operational research - Veerapu, Nagapraveen; Bear, Ravi Kumar Philip; Varikuti, Subbarao; Kurada, Jayakrishna (International Journal of Advances in Medicine, 2020)
Background: Globally, tuberculosis (TB) is one of the leading causes of death. In 2016, 10.4 million people were affected with TB and accounted for 1.7 million deaths. India ranks the first among the seven leading countries that account for 64% of the total burden of TB. To fill the gaps in adherence to therapy and to make the TB Control programs successful, evidence based supplementary low cost effective monitoring tools and techniques are needed. The aims were to determine whether the new sticker tool method acts as supplementary to direct observation component of ‘Directly observed treatment, short course (DOTS) strategy’ used for monitoring adherence to anti-tuberculosis therapy among newly diagnosed sputum positive TB patients; and to compare Sputum smear conversion rate between the intervention group and control group at the end of Intensive phase (IP). Methods: A pragmatic cluster randomized control trial was conducted for a period of 9 months from April 2018 to December 2018 in Rural Khammam district. Data was represented in frequencies and percentages and Means. Results: The delay in sending SMS decreased after field visit (1st week of therapy) but delay again increased as the days passed. The study measured indirectly measured the adherence to the therapy by sputum conversion rate (83.3%). It was noticed that 45.5% stickers did not tally with the date of consumption of TB medications or with the date of sticking on the sticker chart. Conclusions: The study shows self administration is also a good option. There may be other factors that play an important role in adherence to anti tuberculosis treatment (ATT).